Physical Behaviour of Wood Plastice Composite Made of Recycled High-Density Polyethylene (HDPE) - Rahayu, Yuyu; Setiawan, Wahyu; Endra Gunawan; Susilo Budi Husodo (JURNAL KEHUTANAN PAPUASIA, 2023)
This paper investigated the physical characteristics of wood–plastic composites, which were made using recycled high-density polyethylene (HDPE) and using wood flour from Pometia sp (Matoa), Intsia sp (Merbau) and Alstonia sp (Pulai) as filler. The sawdust was taken from local furniture industry and the HDPE was collected from recycled plastic bottles of mineral water. Composite panels were made from recycled HDPE through hot-press moulding produced excellent stability based on JIS and SNI Standard, especially for moisture content and swelling characteristics. The water absorption and targeted density were also measured. In this study we found that the water absorption and the density of the composite exceeded our expectation. The composites showed high variation average for water absorption. For the swelling behavior, the value is varied from 5.74% to 25.57% after 2 hours soaking and varied between 7.56% to 28.53% after 24 hours soaking. This study has shown the composites had a high possibility to be used for interior and non-structural purposes.